Phytohormone Cross-Talk Synthesizes Glycoalkaloids in Potato (Solanum tuberosum L.) in Response to Aphid (Myzus persicae Sulzer) Infestation under Drought Stress - Quandahor, Peter (Insects, 2020)
SIMPLE SUMMARY: Potato (Solanum tuberosum L.) is a vegetable crop that plays a major role in global food security. However, its production and sustainability are adversely affected due to aphid infestation. The green peach aphid, Myzus persicae (Sulzer), poses a significant threat to potato plants globally due to its high production of honeydew and transmission of viruses. Other researchers reported that drought severity could result in an outbreak of insect pests such as aphids. Accordingly, understanding the mechanism of host plant defense against aphids under drought stress is a major concern for insect pest management. This study was conducted to examine the cross-talk of phytohormones in potato glycoalkaloids’ defense against green peach aphids under greenhouse conditions. The results showed that under drought conditions, the cross-talks of phytohormones do not only function as signal hormones, but also modify host plant secondary metabolites to defend against sap-sucking insects. Many potato cultivars may activate phytohormones under drought stress; however, only host plants with a greater level of secondary metabolites may be able to defend against aphid attack. This research will provide a scientific basis for the development of potato varieties with high yield, improved quality, and drought and pest resistance. ABSTRACT: Potato production is adversely affected by aphid infestation across the globe. Understanding the mechanism of host plant defense against aphids under drought stress is paramount for insect pest management. This study was conducted to examine the cross-talk of phytohormones in potato glycoalkaloids’ defense against green peach aphids under greenhouse conditions. A 3 × 2 × 2 factorial experiment comprising three potato cultivars (Qingshu 9, Longshu 3, and Atlantic) and two levels each of water availability and aphid infestation was conducted. The results show that under drought stress, green peach aphids thrive well on host plants, which contain a relatively high water content. The resistant cultivar DXY, which exhibited a higher level of phytohormones, also demonstrated higher α-chaconine and α-solanine contents in both leaf and root, under drought and aphid stress. Conversely, the susceptible cultivar QS9, which exhibited a lower level of phytohormones, also demonstrated low α-chaconine and α-solanine contents in both leaf and root, under drought and aphid stress. The DXY cultivar, which possessed high resistant traits such as α-chaconine and α-solanine, can be used in areas where green peach aphid infestation is a major setback.